Computer anxiety its determinants and its relationship to library anxiety - Salvador, Ma. Criselda R.; Dela Torre, Nathalie N. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The study is concerned with determining if the independent variables - age, sex, course, type of computer experience, pleasantness/unpleasantness of computer experience, reason for computer use, frequency of student's library use, frequency of computer use in the library and frequency of computer use outside the library-influence the level of computer anxiety and library anxiety of the U.P. students.
The study determined the following: (1) level of computer anxiety and library anxiety of the U.P. students, (2) effect of the independent variables on computer anxiety, and (3) correlation between computer anxiety and library anxiety. The study was conducted using survey method. The three-part questionnaire, of which consists of the Computer Anxiety Scale and Library anxiety Scale, was given to 384 U.P. students (undergraduate and graduate) from different courses. With the aid of Statistical Package for Social Science (SPSS), factor analysis with varimax rotation was applied to the two scales to extract significant factors and remove the insignificant ones. Based on the factor analysis, a model of computing the level of anxieties was derived for each scale.
The study revealed that there still exists computer anxiety for some U.P. students. Of all the given variables, only course and frequency of computer use outside the library influence computer anxiety. A level of correlation is positive for computer anxiety scale and library anxiety scale. It was discovered that there are more students who are using computers outside the library frequently that were found to be mostly library anxious and least computer anxious. Factor analysis of computer anxiety scale and library anxiety scale further revealed underlying dimensions of factors that affect the two anxieties.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Anxiety; Library users -- Philippines -- Quezon City; College students -- Philippines -- Quezon City; Graduate students -- Philippines -- Quezon City